Designing of Lab-scale Anaerobic Digester Equipped with Maxblend Impeller to Evaluate Effect of Mixing on Anaerobic Digestion - Buta, Singh; Szamosi, Zoltán; Siménfalvi, Zoltán (International Journal of Engineering and Management Sciences, 2019)
Operational parameters can be easily controlled at lab scale experiments for an anaerobic digestion process. Our aim is to design a lab-scale digester equipped with an impeller to investigate how the geometry of impeller and different mixing modes effect the biogas yield of digester. Further, the methods of measuring the gas volume, gas composition, mixing intensity, torque, temperature are discussed in this article. The assembling of 4 liters digester is described which can be operated at various operating parameters which control the anaerobic digestion process. Mixing is very important to enhance efficiency of an anaerobic digester. To attain mixing Maxblend impeller is used in this lab-scale digester due to its better performance for mixing and power consumption. Various design consideration has been described.